Immobility and mobility in architecture - Kapustin, Petr (project baikal, 2022)
Stability that has been embodied by architecture for centuries now faces the challenges of total dynamism. The tendencies of artification of the world, including those in the previously unthinkable fields, have gained momentum. The author believes that today, architecture is facing the demand to make a new historical choice: to restore itself as a bearer of enduring values of habitat or to dissolve together with the whole civilization in the accelerating stream of uncontrollable changes. This is the main subject of this article.